2020
DOI: 10.1111/bcpt.13451
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoredoxin interaction with flightless‐I/actin complex is differentially altered in alcoholic liver disease

Abstract: Alcoholic liver disease (ALD) may be attributed to multiple hits driving several alterations. The aim of this work was to determine whether nucleoredoxin (NXN) interacts with flightless-I (FLII)/actin complex and how this ternary complex is altered during ALD progression induced by different ALD models. ALD was recapitulated in C57BL/6J female mice by the well-known ALD Lieber-DeCarli model, and by an in vitro human co-culture system overexpressing NXN. The effects of ethanol and low doses of lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In mice experiments, it was also evident that the liver of the "heavy drinking" mice, but not the "light drinking" mice, underwent obvious cell proliferation. This is consistent with the previous finding that the expression of Ki67 in the liver was upregulated by alcohol [ 34 ]. This is likely due to liver regeneration after heavy alcohol consumption.…”
Section: Discussionsupporting
confidence: 94%
“…In mice experiments, it was also evident that the liver of the "heavy drinking" mice, but not the "light drinking" mice, underwent obvious cell proliferation. This is consistent with the previous finding that the expression of Ki67 in the liver was upregulated by alcohol [ 34 ]. This is likely due to liver regeneration after heavy alcohol consumption.…”
Section: Discussionsupporting
confidence: 94%
“…NRX and its subfamily members (RdCVF and C9orf121, but not TRX) may have a common role through their interaction with Flii in TLR4/MyD88 signaling pathway (Hayashi et al, 2010). The ability of NRX and Flii to form a ternary complex with actin is disrupted by ethanol contributing to the progression of alcoholic liver disease in mice, which is also characterized by altered MyD88/TLR4 expression (Alarcon-Sanchez et al, 2020). Both RdCVF and NRX link Flii to MyD88, and synergistically prevent LPS-induced MyD88/TLR4 NFκB activation (Hayashi et al, 2010).…”
Section: Flii and The Immune Responsementioning
confidence: 99%
“…Dysregulation of NXN has been indicated to increase the expression of fibrogenic genes [15,16]. Moreover, deficiency of NXN was observed to result in the progression of alcoholic liver disease (ALD) [26,27]. However, NXN overexpression partially reversed these alterations and reduced liver injury, indicating that NXN played an important role in maintaining tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…As an enzyme, NXN might exhibit its functions by protein-protein interactions network. It was reported that NXN regulated ethanol-associated ALD progression by binding to FLII/actin or MYD88 [26,27]. By expelling KLHL12 from DVL protein, NXN resulted in the inhibition of Dvl ubiquitination to suppress the Wnt/β-catenin signaling [14].…”
Section: Discussionmentioning
confidence: 99%